Opening mathematics texts: A critical discourse analysis of probability problems in mathematics textbook - Bustang Bustang (Beta: Jurnal Tadris Matematika, 2023)
[English]: This article investigates the nature of probability problems presented in mathematics textbook using the socio-political perspective and critical discourse analysis drawn from well-known critical linguists Norman Fairclough. Specifically, the paper analyzed how the students are positioned by the problems presented in the text, to find out the role of authors and student readers, and to gain insight about the possible consequences for students. Drawing on Fairclough's three-dimensional model for critical discourse analysis as a framework for studying the relationship between the written text of probability problems in the textbook, the associated discursive practices, and the social practice to which the discursive practices form part, the article argues that the textbook authors tend to be authoritative by directing students about what to do and how to do the probability (mathematical) activities. The analysis also shows that the use of real-word problems in the text points out the attempts of the authors to present the probability concepts more relevant and accessible to the student readers. The article demonstrates the usefulness of Fairclough's three-dimensional model as a framework for analyzing probability problems presented in the mathematics textbook. [Bahasa]: Artikel ini menyelidiki sifat masalah peluang yang disajikan dalam buku teks matematika dengan menggunakan perspektif sosio-politik dan analisis wacana kritis yang diambil dari ahli bahasa kritis terkenal Norman Fairclough. Secara khusus, makalah ini menganalisis bagaimana siswa diposisikan oleh masalah yang disajikan dalam teks, untuk mengetahui peran penulis dan siswa sebagai pembaca, serta untuk mendapatkan wawasan tentang konsekuensi yang mungkin terjadi pada siswa. Merujuk pada model tiga dimensi Fairclough untuk analisis wacana kritis sebagai kerangka kerja untuk mempelajari hubungan antara teks tertulis dari masalah peluang dalam buku teks, praktik diskursif yang terkait, dan praktik sosial yang merupakan bagian dari praktik diskursif, artikel ini menunjukkan bahwa penulis buku teks cenderung otoriter dengan mengarahkan siswa tentang apa yang harus dilakukan dan bagaimana melakukan kegiatan berkaitan dengan konsep peluang (matematika). Analisis juga menunjukkan bahwa penggunaan masalah berbasis kehidupan sehari-hari dalam teks menunjukkan upaya penulis untuk menyajikan konsep peluang yang lebih relevan dan dapat diakses oleh siswa. Artikel ini menunjukkan kegunaan model tiga dimensi Fairclough sebagai kerangka kerja untuk menganalisis masalah peluang yang disajikan dalam buku teks matematika.